Assessment of minerals in phoenix dactylifera l. As determined by inductively coupled plasma optical emission spectrometry using ANOVA and PCA - Badarusham K.; Sabri N.E.; Salvamani S.; Hassan M.S.; Hassan Z.; Hashim R. (Blue Eyes Intelligence Engineering and Sciences Publication, 2024)
Indexed by Scopus